Clinical study of cardiovascular involvement in patients with hypothyroidism - Kishan, U.; Krishna, J. Gopala (International Journal of Advances in Medicine, 2019)
Background: Hypothyroidism is usually associated with the involvement of the cardiovascular system in the form of the cardiac abnormalities. The Research data on this has been found to be limited. The dysfunction of the cardiac caused by hypothyroidism is usually reversible. Objective was to study the incidence of cardiac abnormalities in patients with hypothyroidism. Methods: Total 40 confirmed cases of hypothyroid disease were included in the present study. General investigations, ECG, ECHO was done in all the patients to assess for cardiovascular involvement. The data was entered in the Microsoft Excel worksheet and analysed using proportions. Results: One fourth of the patients were found to have the bradycardia. The Delayed ankle jerk was seen in 67.5% of the cases and the next common CNS manifestation was the hoarseness of the voice. 30% of the case had normal ECG findings. 40% of the cases had the bradycardia. 35% of the cases had the low voltage complexes. 32.5% of the cases had the normal ECHO reports. 27.5% of the cases had the pericardial effusion. Same proportion of the cases were found to have the diastolic dysfunction. But most of them had the dysfunction and the severe cases were found to be very few. Only two patients had IVS thickness. Conclusions: Majority of the cases of the hypothyroidism in the present study were found to have the cardiovascular involvement. This points towards the importance of the early diagnosis of hypothyroidism and the prevention of complications like the cardiovascular system and the central nervous system involvement.